Presence of multi-drug resistant pathogenic Escherichia coli in the San Pedro River located in the State of Aguascalientes, Mexico - Ramirez Castillo, Flor Y.; Avelar González, Francisco J.; Garneau, Philippe; Marquez Diaz, Francisco; Guerrero Barrera, Alma L.; Harel, Josée (Frontiers in Microbiology, 2013)
Contamination of surface waters in developing countries is a great concern. Treated and untreated wastewaters have been discharged into rivers and streams, leading to possible waterborne infection outbreaks and may represent a significant dissemination mechanism of antibiotic resistance genes. In this study, the water quality of San Pedro River, the main river and pluvial collector of the Aguascalientes State, Mexico was assessed. Thirty sample locations were tested throughout the River. The main physicochemical parameters of water were evaluated. Results showed high levels of fecal pollution as well as inorganic and organic matter abundant enough to support the heterotrophic growth of microorganisms. These results indicate poor water quality in samples from different locations. One hundred and fifty Escherichia coli were collected and screened by PCR for several virulence genes. Isolates were classified as either pathogenic (n = 91) or commensal (n = 59). The disc diffusion method was used to determine antimicrobial susceptibility to 13 antibiotics. Fifty-two percent of the isolates were resistant to at least one antimicrobial agent and 30.6% were multi-resistant. Eighteen E. coli strains were quinolone resistant of which 16 were multi-resistant. Plasmid-mediated quinolone resistance (PMQR) genes were detected in 12 isolates. Mutations at the Ser-83→Leu and/or Asp-87→Asn in the gyrA gene were detected as well as mutations at the Ser-80→Ile in parC. An E. coli microarray (Maxivirulence V 3.1) was used to characterize the virulence and antimicrobial resistance genes profiles of the fluoroquinolone-resistant isolates. Antimicrobial resistance genes such as blaTEM, sulI, sulII, dhfrIX, aph3 (strA), and tet (B) as well as integrons were found in fluoroquinolone (FQ) resistance E. coli strains. The presence of potential pathogenic E. coli and antibiotic resistance in San Pedro River such as FQ resistant E. coli could pose a potential threat to human and animal health.